Protecting healthcare workers during COVID-19 pandemic through health protocol guidelines in Maluku, Indonesia - Frangky Ertanto; Robiana Modjo; Riskiyana Sukandhi Putra (BKM Public Health and Community Medicine, 2021)
Purpose: This study aims to describe the implementation of two ministerial decrees stipulated by The Ministry of the Health Republic of Indonesia that may serve as Health Protocol Guidelines in Maluku, Indonesia. Method: Cross-sectional with a quantitative and qualitative approach was conducted from March to August 2021. Self-administered questions are sent to respondents and interviews will be conducted where confirmation was found necessary. Result: Implementation of Health Protocol Guidelines in five healthcare providers in Maluku was found to be good and very good as indicated by the total score of the overall implementation. Conclusion: This study revealed that protection measures taken and adopted from Health Protocol Guidelines issued by Indonesian were well implemented. However, future improvement might be necessary to maintain the current implementation even after the pandemic ends.